Applicability of bankruptcy prediction models in the western Hungarian food retail sector - Patyi Balázs; Szóka Károly; Pataki László; Поті Б.; Потокі Л. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. The article examines the applicability of existing bankruptcy prediction models in the food retail sector. The industry has been chosen for analysis due to the fact, that according to official statistics, it has been significantly affected by the events of recent years (Covid-19 epidemic and economic crisises). For the study, a database was created with all firms that had ceased to operate in the sector over an 11-year period in 3 counties. The main objectives of the study were: 1) to check whether there are differences in the reliability of the models and which models are most applicable to the selected sector; 2) to investigate the accuracy of the models over the time horizons of bankruptcy; 3) to check the accuracy of forecasting models by type of bankruptcy completion procedure; 4) provide suggestions on the possibilities of applying bankruptcy forecasting models and indicate directions for further research. During the research, it was found that not all considered models are suitable for accurate forecasting. Two of the five models have very low prediction accuracy (Virág-Hajdu model and Tafler model). Assessment of model accuracy across bankruptcy time horizons showed that there is little variation in short-term forecast accuracy, with a slight decrease in the reliability of the models in the long term. Examining the predictive accuracy of the models by completion procedure type revealed that the types of procedures affected the prediction. The most accurate results were obtained for liquidation, while voluntary liquidation was the least accurate in several cases. The use of bankruptcy prediction models is important for an enterprise because they are a key tool for reducing its operational risk and preventing financial problems. The study can provide information for businesses in the food retail sector and the results can be used for further research. There are additional opportunities for expanding the enterprise database, transferring the research to other sectors of the economy, and expanding the number of bankruptcy models to study the suitability of their application to enterprises of various industries.

A cikk az élelmiszerkiskereskedelmi ágazatban vizsgálja a csődelőrejlző modellek alkalmazhatóságát. Az elemzéshez egy olyan iparág került kiválasztásra, amelyet az elmúlt évek eseményei (Covid-19 járvány, gazdasági válság) jelentős mértékben érintettek. Így a döntés a hivatalos statisztikákkal alátámasztva az élelmiszerkiskereskedelem ágazatra esett. A vizsgálathoz kiépítésre került egy adatbázis, amely 11 éves időtávra tartalmazza az ágazatban tevékenykedő összes megszűnt céget 3 megyére vonatkozóan. A tanulmányban négy fő kutatási cél került elkülönítésre. Vizsgálatra került, hogy az egyes modellek megbízhatósága között vannak-e eltérések és mely modellek alkalmazhatók legjobban a vizsgált ágazatra. Ennek alapján kiderült, hogy a vizsgált modellekből nem mindegyik alkalmas a pontos előrejelzésre. A vizsgált öt modell közül kettő esetében nagyon alacsony az előrejelzés pontossága. Szintén a vizsgálat tárgya volt a modellek előrejelzési pontossága a csőd bekövetkezési időtávokra vonatkozóan. Itt megállapításra került, hogy a rövidtávú előrejelzés pontosságában csekély eltérés tapasztalható, hosszú távon kis mértékben csökken a modellek megbízhatósága. Ezt követő vizsgálat a modellek előrejelzési pontosságával kapcsolatos a megszűnési eljárási típusok szerint. Megállapításra került, hogy az eljárási típusok hatással vannak az előrejelzésre. Legpontosabb eredmény felszámolás esetén van, míg a legpontatlanabbnak több esetben is a végelszámolás bizonyult. Végül a kapott eredmények alapján javaslatok lettek téve a csődmodellek alkalmazhatóságára vonatkozóan és ki lett jelölve a további kutatási irány is. A csődelőrejelző modellek alkalmazása a vállalkozások életében nagyon fontos, hiszen a vállalkozás működési kockázatának csökkentése szempontjából és a problémák előrejelzése végett kulcsfontosságú eszköz a csődmodell. A kutatás információval szolgálhat az ágazatban működő vállalkozások számára, valamint további kutatásokhoz is alapul szolgálhat. Az adatbázis bővítése, más ágazatok vizsgálata és új modellek alkalmazása további lehetőségeket rejt a csődmodellek alkalmazhatóságának a kérdéskörében.

Резюме. У статті досліджується придатність до застосування існуючих моделей прогнозування банкрутства в секторі роздрібної торгівлі продуктами харчування. Для аналізу була обрана галузь, яка, за даними офіційної статистики, суттєво постраждала від подій останніх років (епідемія Covid-19, економічна криза). Для дослідження була створена база даних з усіма фірмами, які припинили свою діяльність у секторі протягом 11 років у 3 областях (медьє). Для дослідження визначено чотири основні цілі: 1) перевірити, чи існують відмінності в надійності моделей і які моделі найбільше застосовні до вибраного сектора; 2) вивчити точність моделей за часовими межами банкрутства; 3) перевірити точність прогнозування моделей за типом процедури завершення банкрутства; 4) надати пропозиції щодо можливостей застосування моделей прогнозування банкрутства та вказати напрями подальших досліджень. У процесі дослідження виявлено, що не всі розглянуті моделі придатні для точного прогнозування. Дві з п'яти моделей мають дуже низьку точність прогнозування (модель Віраг-Гойду та модель Тафлера). Оцінка точності моделей за межами часових горизонтів банкрутства показала, що існує незначна варіація в точності короткострокового прогнозу з незначним зниженням надійності моделей у довгостроковій перспективі. Перевірка точності прогнозування моделей за типом процедури завершення виявила, що типи процедур впливають на прогноз. Найбільш точні результати отримані для ліквідації, тоді як добровільна ліквідація виявилася найменш точною в кількох випадках. Використання моделей прогнозування банкрутства є важливим для підприємства, оскільки вони є ключовим інструментом для зниження його операційного ризику та попередження фінансових проблем. Дослідження може надати інформацію для підприємств у секторі роздрібної торгівлі продуктами харчування, а результати можуть бути використані для подальших досліджень. Існують додаткові можливості для розширення бази даних підприємств, перенесення дослідження на інші сектори економіки і розширення кількості моделей банкрутства для вивчення придатності їх застосування до підприємств різних галузей.
Застосовність моделей прогнозування банкрутства в секторі роздрібної продовольчої продукції західної Угорщини
Csődelőrejelző modellek alkalmazhatósága a nyugat-magyarországi élelmiszer-kiskereskedelmi szektorban
https://aab-economics.kmf.uz.ua/aabe/issue/view/4
Keywords: bankruptcy prediction models; crisis; sectoral analysis; time series analysis